Physical chemical properties and cell toxicity of sanding copper-treated lumber. Issue 4 (3rd April 2018) - Sisler, Jennifer D.; Qi, Chaolong; McKinney, Walter; Shaffer, Justine; Andrew, Michael; Lee, Taekhee; Thomas, Treye; Castranova, Vincent; Mercer, Robert R.; Qian, Yong
Abstract: To protect against decay and fungal invasion into the wood, the micronized copper, copper carbonate particles, has been applied in the wood treatment in recent years; however, there is little information on the health risk associated with sanding micronized copper-treated lumber. In this study, wood dust from the sanding of micronized copper azole-treated lumber (MCA) was compared to sanding dust from solubilized copper azole-treated wood (CA-C) and untreated yellow pine (UYP). The test found that sanding MCA released a much higher concentration of nanoparticles than sanding CA-C and UYP, and the particles between about 0.4–2 µm from sanding MCA had the highest percentage of copper. The percentage of copper in the airborne dust from sanding CA-C had a weak dependency on particle size and was lower than that from sanding MCA. Nanoparticles were seen in the MCA PM2.5 particles, while none were detected in the UYP or CA-C. Inductively coupled plasma mass spectrometry (ICP-MS) analysis found that the bulk lumber for MCA and CA-C had relatively equal copper content; however, the PM2.5 particles from sanding the MCA had a higher copper concentration when compared to the PM2.5 particles from sanding UYP or CA-C. The cellular toxicity assays show that exposure of RAW 264.7 macrophages (RAW) to MCA and CA-C wood dust suspensions did not induce cellular toxicity even at the concentration of 200 µg PM2.5 wood dust/mL. Since the copper from the treated wood dust can leach into the wood dust supernatant, the supernatants of MCA, CA-C and UYP wood dusts were subjected to the cellular toxicity assays. The data showed that at the higher concentrations of copper (≥5 µg/ml), both MCA and CA-C supernatants induced cellular toxicity. This study suggests that sanding MCA-treated lumber releases copper nanoparticles and both the MCA and CA-C-treated lumber can release copper, which are potentially related to the observed in vitro toxicity.